Gaya Pola Asuh Orang Tua Pada Anak di Desa Curug Wetan - Neneng Alawiyah; Septia Henefryani; Sonia Tri Rezkipuan Maharani; Ghina Amalia Cintami; Eri Miftahul Jannah; Saskia Nurhaliza; Aulia Rahmadina; Sifah Fauziah; Indah Julianti; Zahra Rennuat (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to increase the knowledge of parents in Curug Wetan Village regarding the application of good parenting styles in children. This activity was motivated by the many applications of authoritarian parenting in children. The research method used in this activity is carried out by providing insight strengthening in the form of lectures and discussions. The participants of the activity who attended were several parents in Curug Wetan Village who also attended Posyandu activities. This activity took place on December 7, 2023, offline at Posyandu Kenanga IV, Curug Wetan Village. The material presentation in the form of parenting styles for children. The existence of this activity is expected to be able to increase parents' knowledge about what kind of parenting should be applied to families, especially children, to form children's character following the characteristics that have been described by psychologists.